Innovation During COVID-19: Improving Addiction Treatment Access. Issue 4 (July 2020) - Samuels, Elizabeth A.; Clark, Seth A.; Wunsch, Caroline; Jordison Keeler, Lee Ann; Reddy, Neha; Vanjani, Rahul; Wightman, Rachel S.
Abstract : N/A: During the COVID-19 pandemic, many addiction treatment and harm reduction organizations have had to reduce their hours and services for people with substance use disorders, placing these individuals at increased risk of death. In order to address restricted treatment access during COVID-19, guidance from the Substance Abuse Mental Health Services Administration, the US Drug Enforcement Administration, and the US Department of Health and Human Services has allowed for use of audio-only telehealth encounters for buprenorphine induction without requiring an in-person evaluation or video interface. This has enabled innovations in order to try to meet the needs of the most vulnerable among us during the current pandemic. In this new regulatory environment, we established the Rhode Island Buprenorphine Hotline, a phone hotline which functions as a "tele-bridge" clinic where people with moderate to severe opioid use disorder can be linked with a DATA 2000 waivered provider who can provide an initial assessment and, if appropriate, prescribe buprenorphine for unobserved induction and linkage to outpatient treatment. In this correspondence we briefly share our experience developing this common sense approach to addressing the complex problem of access to treatment only now permissible due to regulatory changes during COVID-19.